Mechanical Strength and Fatigue Fracture Analysis on Al-Zn-Mg Alloy with the Influence of Creep Aging Process - Ponnusamy, Muruganantham; Pulla, Bhanu Pratap; Sathish, T.; Karthikeyan, Sivakumar; Ravindran, S.; Pattanaik, Balachandra; Subbiah, Ram (Advances in materials science and engineering, 2021)
The Al-Zn-Mg alloy comes under the aluminium alloy; it possesses good capability of age hardening and superior strength in contrast to other alloys. The numbers of creep aging experiments are conducted with the support of different temperature levels such as 180, 200, and 2000°C. The effects of tests are reflected on the tensile test and fatigue tests; the temperature and stress directly affects the creep characteristics, mechanical strength, and fatigue performance of the Al-Zn-Mg alloy. The time period of the creep test is maintained as 15 hrs with constant load of 200 MPa and 220 MPa. The increasing temperature increases the tensile strength and fatigue life of the Al-Zn-Mg alloy under initial condition; furthermore, continuous increment reduces the strength and fatigue existence. In the fatigue test, the fatigue span of the Al-Zn-Mg is extremely enhanced by the application of creep aging at a particular temperature. The 3D profilometry image visibly shows the influence of temperature in forming a fracture in fatigue analysis through microstructure analysis.